Performance of Wood Chips/Peanut Shells Biofilters Used to Remove Organic Matter from Domestic Wastewater - Villamar-Ayala, C (Elsevier B.V., 2020)
Biofiltration is one of the main alternatives developed to improve wastewater quality and increase its recyclability. Support materials are extremely important when using this technology since they impact the cost of the treatment. In this work, we study the use of wood chips/peanut shell as support medium within biofilters incorporating microorganisms (BM), plants and microorganisms (BPM), earthworms and microorganisms (BEM) and all organisms (hybrid biofilters, HB). These typologies were evaluated to remove organic matter from synthetic domestic wastewater. For this purpose, twelve biofilters were operated in parallel under three different nominal hydraulic rates (0.5, 1 and 1.5 m3 m−2 day−1). Previously, support materials were individually characterized and acute/chronic toxicity tests on plants (Eleocharis palustris (L.) Roem. & Schult.) and earthworms (Eisenia foetida Savigny) were driven. Results showed that both materials have good adsorbent properties, providing adequate environmental conditions for biofiltration. Moreover, non toxicological response was reported when a 25 v/v % peanut shell fraction was selected. With this fraction used in every biofilter studied, the average hydraulic conductivity was between 321 and 502 mm h−1, reaching organic matter removal efficiencies close to 80% (measured as COD), and between 40 and 63% (measured as VS). Higher efficiencies, attributed to the longer contact times, and lower clogging were observed at lower hydraulic rates. The incorporation of earthworms and plants improved the solids removal and reduced clogging. The statistical analysis indicated that the results obtained for biofilters operating at 0.5 m3 m−2 day−1 showed significant differences (p < 0.05) with respect to the other rates. Moreover, BEM were the ones that presented significant differences. As a conclusion, low-cost organic materials (wood chip/peanut shell mix) can be successfully used as support medium, since they provide adequate environmental conditions for plants and earthworms, improving the operation and maintaining contaminant (organic matter) removal within biofiltration typologies. © 2018 Elsevier B.V.